Two new elongate unpatterned moray eels from Taiwan and Vietnam, with notes on two congeners (Anguilliformes: Muraenidae) - Smith, David G.; Hibino, Yusuke; Ho, Hsuan-Ching (Zootaxa, 2018)
Two new species of elongate unpatterned moray eels related to Gymnothorax prolatus are described. Gymnothorax pseudoprolatus sp. nov. is described from one specimen collected off southwestern Taiwan and Gymnothorax vietnamensis sp. nov. is described from seven specimens collected off central Vietnam. Both differ from other species in the group in the number of vertebrae, position of anus, and dentition. Gymnothorax pseudomelanosomatus Loh et al., 2015 is reported from southern Taiwan for the first time; it was previously known from the type series collected off the northeastern tip of Taiwan. Gymnothorax angusticauda (Weber & de Beaufort 1916) is reported for the first time in Taiwan and the Philippines.